The association of alcohol use with all‐cause and cardiovascular disease‐related hospitalizations or death in older, high‐risk Veterans. (4th May 2021) - Blalock, Dan V.; Grubber, Janet; Smith, Valerie A.; Zulman, Donna M.; Weidenbacher, Hollis J.; Greene, Liberty; Dedert, Eric A.; Maciejewski, Matthew L.
Abstract: Background: The prevalence of alcohol misuse among older adults has grown dramatically in the past decade, yet little is known about the association of alcohol misuse with hospitalization and death in this patient population. Methods: We examined the association between alcohol use (measured by a screening instrument in primary care) and rates of all‐cause and cardiovascular disease (CVD)‐related 6‐month hospitalization or death via electronic health records (EHRs) in a nationally representative sample of older, high‐risk Veterans. Models were adjusted for sociodemographic and clinical characteristics, including frailty and comorbid conditions. Results: The all‐cause hospitalization or death rate at 6 months was 14.9%, and the CVD‐related hospitalization or death rate was 1.8%. In adjusted analyses, all‐cause hospitalization or death was higher in older Veterans who were nondrinkers or harmful use drinkers compared to moderate use drinkers, but CVD‐related hospitalization or death was similar in all categories of drinking. Conclusions: These findings suggest that the complex association between alcohol and all‐cause acute healthcare utilization found in the broader population is similar in older, high‐risk Veteran patients. These findings do not support an association between alcohol consumption and CVD‐specific hospitalizations. Abstract : In a nationally representative sample of older, high‐risk Veterans' electronic health records, all‐cause hospitalization or death was higher in older Veterans that were non‐drinkers or harmful use drinkers compared to moderate use drinkers, but CVD‐related hospitalization or death was similar in all categories of drinking. The complex association between alcohol and hospitalization or death found in the broader population is similar in older, high‐risk Veterans with already elevated risk of hospitalization or death.